PENGEMBANGAN EDIBLE FILM BERBASIS PATI TALAS TERMODIFIKASI SECARA CROSS - LINKING MENGGUNAKAN SODIUM TRIPOLYPHOSPHATE DENGAN PLASTISIZER GLISEROL - Ria Ulfiasari; Rini Umiyati; Umar Hafidz Asy'ari Hasbullah (AGROINTEK, 2021)
Plastic as food packaging had less beneficial properties besides being harmful to health and not environmentally friendly. The use of taro starch based edible film was expected to solve this problem. The purpose of this study was to study the use of taro modified starch with sodium tripolyphosphate (STPP) as crosslinking agent and glycerol as a plasticizer to physical and mechanical characteristics in making edible films.  Experimental design was carried out using differences in concentration of modified starch 3%, 5%, and 7% and glycerol concentrations of 10%, 30%, and 50%. The results showed that the use of modified taro starch and glycerol in the edible film formulation had a good impact on the properties of the film by decreasing the water vapor transmission rate and increasing the solubility of the film.